2022
DOI: 10.1002/rth2.12783
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and knowledge gaps facing hemophilia carriers today: Perspectives from patients and health care providers

Abstract: Background Hemophilia carriers experience abnormal bleeding symptoms; however, a lack of awareness about this topic coupled with additional knowledge gaps and barriers leads to suboptimal care for this population. Objective The primary objective was to describe the current knowledge gaps and challenges from the perspective of both hemophilia carriers and their health care providers. Methods We carried out a mixed methods descriptive study with two population groups between September and December 2020. The hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…This study found that privacy, expense, and a fear of positive results affected the choice of female relatives of PWH regarding participation in genetic testing, consistent with the findings of Punt et al and Chaigneau et al 23 , 48 These results suggest that when conducting genetic testing, it is necessary to ensure the security of the genetic information for the whole family, 49 and relevant departments should improve personal privacy protection policies, strengthen the awareness of medical safety precautions among medical workers, and eliminate the concerns of hemophiliac families about the inappropriate use of their genetic information. Professional medical and nursing teams should be organized to expand specialist training and assessment in genetics, improve genetic testing techniques, and report the interpretation ability of medical workers, to provide comprehensive and systematic genetic guidance and prompt high-risk groups to overcome their fear and negative emotions.…”
Section: Discussionsupporting
confidence: 89%
“…This study found that privacy, expense, and a fear of positive results affected the choice of female relatives of PWH regarding participation in genetic testing, consistent with the findings of Punt et al and Chaigneau et al 23 , 48 These results suggest that when conducting genetic testing, it is necessary to ensure the security of the genetic information for the whole family, 49 and relevant departments should improve personal privacy protection policies, strengthen the awareness of medical safety precautions among medical workers, and eliminate the concerns of hemophiliac families about the inappropriate use of their genetic information. Professional medical and nursing teams should be organized to expand specialist training and assessment in genetics, improve genetic testing techniques, and report the interpretation ability of medical workers, to provide comprehensive and systematic genetic guidance and prompt high-risk groups to overcome their fear and negative emotions.…”
Section: Discussionsupporting
confidence: 89%
“…Several sources have recommended testing at risk females for hemophilia as soon as feasible to allow appropriate management for procedures, bleeding episodes, trauma, and life planning. 26 , 27 , 28 It would be prudent to continue studying females with hemophilia on a larger scale, develop evidence-based guidelines, training of health care professional and families, and developing further research for females with hemophilia so that diagnosis is not delayed. Whether prophylaxis was started in relation to a bleeding complication vs following diagnosis was not recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect for improvement is that the level of knowledge of health professionals about hemophilia is low and sometimes limiting when it comes to the clinical approach, as observed in the study by Chaigneau et al [ 40 ].…”
Section: Discussionmentioning
confidence: 99%